Assessing the need for transfer to the intensive care unit for Coronavirus-19 disease: Epidemiology and risk factors. (November 2020) - Hashmi, Muhammad Daniyal; Alnababteh, Muhtadi; Vedantam, Karthik; Alunikummannil, Jojo; Oweis, Emil S.; Shorr, Andrew F.
Abstract: Background: Although many patients with coronavirus disease 2019 (Covid-19) require direct admission to the intensive care unit (ICU), some are sent after admission. Clinicians require an understanding of this phenomenon and various risk stratification approaches for recognizing these subjects. Methods: We examined all Covid-19 patients sent initially to a ward who subsequently required care in the ICU. We examined the timing transfer and attempted to develop a risk score based on baseline variables to predict progressive disease. We evaluated the utility of the CURB-65 score at identifying the need for ICU transfer. Results: The cohort included 245 subjects (mean age 59.0 ± 14.2 years, 61.2% male) and 20% were eventually sent to the ICU. The median time to transfer was 2.5 days. Approximately 1/3rd of patients were not moved until day 4 or later and the main reason for transfer (79.2%) was worsening respiratory failure. A baseline absolute lymphocyte count (ALC) of ≤0.8 10 3 /ml and a serum ferritin ≥1000 ng/ml were independently associated with ICU transfer. Co-morbid illnesses did not correlate with eventual ICU care. Neither a risk score based on a low ALC and/or high ferritin nor the CURB-65 score performed well at predicting need for transfer. Conclusion: Covid-19 patients admitted to general wards face a significant risk for deterioration necessitating ICU admission and respiratory failure can occur late in this disease. Neither baseline clinical factors nor the CURB-65 score perform well as screening tests to categorize these subjects as likely to progress to ICU care. Highlights: Nearly 20% of Coronavirs-19 disease patients on general wards eventually require intensive care unit admission. The lymphocyte count & ferritin are associated transfer. Neither factor nor CURB-65 correlates with subsequent ICU care.